2019
DOI: 10.2494/photopolymer.32.457
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Modification on CO<sub>2</sub> Permeability of Polymers of Intrinsic Microporosity / Silica Nanoparticles Composite Membranes

Abstract: High gas permeable polymer membranes are required to achieve carbon dioxide capture and storage with high efficiency. In this study, novel mixed matrix membranes (MMMs) based on a chemically modified polymer of intrinsic microporosity and silica nanoparticles were fabricated, and their gas permeation properties were evaluated. The methyltetrazole -modified polymer of intrinsic microporosity (MTZ-PIM) showed higher CO 2 /N 2 selectivity than the pristine PIM membrane, and their composite membrane with the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, Kaliaguine et al had reported that the gas diffusivity of the 6FDA-DAM-HAB co-polyimide was decreased with adding MIL-53 [24]. Kawakami et al also reported that the addition of the silica nanoparticles reduced the gas diffusivity of the PIM-1 polymer [25]. Therefore, the decrease in the gas The values of the Z2 filled MMMs were reported in our previous study [16].…”
Section: Gas Separation Performancementioning
confidence: 62%
“…However, Kaliaguine et al had reported that the gas diffusivity of the 6FDA-DAM-HAB co-polyimide was decreased with adding MIL-53 [24]. Kawakami et al also reported that the addition of the silica nanoparticles reduced the gas diffusivity of the PIM-1 polymer [25]. Therefore, the decrease in the gas The values of the Z2 filled MMMs were reported in our previous study [16].…”
Section: Gas Separation Performancementioning
confidence: 62%